الاستلزام الحواري في ديوان تسابيـح الليـل لسعد مردف - سهام بلابل; سعاد منصور; مريم زاوش (University of El-Oued جامعة الوادي, 2025)
الملخص: تهدف هذه الدراسة إلى تحليل الاستلزام الحواري في ديوان "تسابيح الليل" للشاعر الجزائري سعد مردف، انطلاقًا من نظرية غرايس في التداولية، التي تركز على انتهاك مبادئ الحوار (الكَم، الكيف، الملاءمة، والجهة) لإنتاج معانٍ ضمنية. اعتمدت الدراسة على المنهج الوصفي التداولي، مع تحليل نماذج شعرية من الديوان الذي يتميز بطابعه الصوفي وارتباطه بمناجاة الذات والخطاب الديني. كشفت النتائج أن الشاعر استخدم أساليب النداء، الأمر، الاستفهام، والخبر لخرق مبادئ التواصل وإنتاج دلالات إيحائية، كما أن المبالغة في الخبر والأمر غير الملائم نقلت مشاعر الندم أو الشوق الروحي. وأظهرت الدراسة أن الاستلزام الحواري يكشف عن طبقات متعددة من المعاني في النص الشعري، مما يبرز تأثيره العميق. Abstract This study aims to analyse conversational implicature in the poetry collection "Tasbeeh Al-Layl" (Night Praises) by the Algerian poet Saad Mirdif, based on Grice’s pragmatic theory, which focuses on violating dialogue principles (quantity, quality, relation, and manner) to produce implied meanings. The study adopted a descriptive-pragmatic approach, analysing poetic samples from the diwan, which is distinguished by its Sufi tone and its connection to self-contemplation and religious discourse. The findings revealed that the poet employed apostrophe, command, apostrophe, command, interrogation, and declarative styles to breach communication principles and generate suggestive meanings. Additionally, exaggeration in declaratives and illogical commands conveyed emotions such as remorse or spiritual longing. The study demonstrated that conversational implicature uncovers multiple layers of meaning in the poetic text, highlighting its profound impact.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: الاستلزام – التداولية – المبادئ; entailment-deliberative-principles